Hematopoietic cell transplantation comorbidity index and risk of developing invasive fungal infections after allografting. (October 2018) - Busca, Alessandro; Passera, Roberto; Maffini, Enrico; Festuccia, Moreno; Brunello, Lucia; Dellacasa, Chiara; Aydin, Semra; Frairia, Chiara; Manetta, Sara; Butera, Sara; Iovino, Giorgia; Giaccone, Luisa; et al.
Abstract We evaluated the potential correlation of the hematopoietic cell transplantation comorbidity index (HCT-CI) with the risk of developing post-transplant invasive fungal infections (IFIs). Between January 2009 and March 2015, 312 consecutive patients who received a first allograft entered the study. Low/intermediate HCT-CI risk score (0–2) was observed in 172/312 (55%), whereas high HCT-CI score (≥3) was seen in 140/312 (45%). Overall, 51/312 (16%) patients experienced IFI, defined as possible in 19 (6%), probable in 27 (9%), and proven in 5 (2%). Cumulative incidence of probable-proven IFI at 1 year was 8.5% with a significant higher incidence in patients with high HCT-CI (12%) vs. those with low-intermediate HCT-CI (5%;p  = 0.006). There was a strong trend for a higher incidence of baseline severe pulmonary comorbidity in patients who developed probable-proven IFI (p  = 0.051). One-year cumulative incidence of non-relapse mortality was higher in patients with IFI vs. those without, 49 and 16% (p  < 0.001). By multivariate analysis, disease status at transplant and high HCT-CI, when combined with acute GVHD, were independently associated with the risk of post-transplant IFI. This study shows that a high HCT-CI predicts the risk of developing IFI and may indicate the need of mold-active antifungal prophylaxis in high-risk patients.